Ammonia intoxication on workplace : case report and a review of literature - Lalić, Hrvoje, liječnik, 1960- (Array, 2009)
Abstract: In December 2003 in Rijeka, Croatia, a work accident happened when in the meat industry »Vir« a forklift damaged the ammonia pipe. Two butchers were acutely poisoned. The objective is to warn of the danger of ammonia and of the need to improve preventive programs of occupational medicine. The method of comparing the two injured workers, i.e. their spirometric values, was used. The results showed progressive diminishing of patients´ respiratory abilities, in the patient with lungs transplanted VC 32%, FVC 33%, FEV1 16% and FEF75%=6% in 2006, the year when he died. In the patient that survived, the values in 2008 were VC 43.5%, FVC 27.2%, FEV1% 56.7% and FEF75%=6%. The patients´ CT showed diffused fibrosing and bronchiectasiae. Obliterating bronchiolitis developed in both patients. The second patient is the lung transplantation candidate. The first patient developed post transplantation cytomegalovirus pneumonia so he fought CMV antigenemia and infection till the end